2020
DOI: 10.1101/2020.04.12.20063032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Effects of Pathological Beta Burst Dynamics Between Parkinson’s Disease Phenotypes Across Different Movements

Abstract: Background: Resting state beta band (13-30 Hz) oscillations represent pathological neural activity in Parkinson's disease (PD). It is unknown whether the peak frequency or dynamics of beta oscillations change among rest, fine, limb and axial movements. This will be critical for the development and feasibility of closed loop deep brain stimulation (DBS) algorithms during resting and movement states. Methods: Subthalamic (STN) local field potentials (LFPs) were recorded from a sensing neurostimulator (Activa PC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The ability to record synchronized neural and kinematic signals in freely moving individuals with PD using the implanted, sensing dBCI (Activa™ PC+S, Medtronic PLC), led to the discovery of neural and kinematic signals that corresponded to abnormal movements such as bradykinesia, gait impairment, and FOG. These recordings have demonstrated that STN beta band power can be tracked during ongoing movement in PD, that the peak frequency of the beta band did not change among rest, or finger, limb and axial movements, and that there was a subject-specific band of elevated beta power that was conserved throughout a variety of gait tasks (Blumenfeld et al, 2017 ; Anidi et al, 2018 ; Neuville et al, 2020 ). These contributions demonstrate that control policy algorithms in closed-loop DBS will be able to track, and do not need to adjust the frequency of, the beta band neural input in freely moving people with PD.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to record synchronized neural and kinematic signals in freely moving individuals with PD using the implanted, sensing dBCI (Activa™ PC+S, Medtronic PLC), led to the discovery of neural and kinematic signals that corresponded to abnormal movements such as bradykinesia, gait impairment, and FOG. These recordings have demonstrated that STN beta band power can be tracked during ongoing movement in PD, that the peak frequency of the beta band did not change among rest, or finger, limb and axial movements, and that there was a subject-specific band of elevated beta power that was conserved throughout a variety of gait tasks (Blumenfeld et al, 2017 ; Anidi et al, 2018 ; Neuville et al, 2020 ). These contributions demonstrate that control policy algorithms in closed-loop DBS will be able to track, and do not need to adjust the frequency of, the beta band neural input in freely moving people with PD.…”
Section: Introductionmentioning
confidence: 99%
“…31 Other studies analyzing spontaneous LFPs during resting, sitting, standing, and walking have found mixed results regarding movement-related STN beta desynchronization. [32][33][34][35][36] Greater mechanistic knowledge about changes in STN field potentials during specific limb movements could lead to a better understanding of the pathophysiology and novel strategies for therapy.…”
mentioning
confidence: 99%
“…One recent study reported that lower and upper limb movement onset coincides with high and low beta desynchronization, respectively, in both STN and motor cortex 31 . Other studies analyzing spontaneous LFPs during resting, sitting, standing, and walking have found mixed results regarding movement‐related STN beta desynchronization 32‐36 . Greater mechanistic knowledge about changes in STN field potentials during specific limb movements could lead to a better understanding of the pathophysiology and novel strategies for therapy.…”
mentioning
confidence: 99%
“…Finally, levels of physical activity are also related to the time of day. This may lead to physiological modulation of beta in response to movements (Jenkinson & Brown, 2011; Kühn et al, 2004; Lofredi et al, 2019; Neuville et al, 2021; Quinn et al, 2015), but will also increase potential artifact sources. It is already known that the heartbeat can affect measures of beta power in certain DBS devices (Neumann et al, 2021; Sorkhabi et al, 2020), and movements themselves present another potential source of transient artifacts in LFP recordings (Hammer et al, 2021; Swann, Hemptinne, Miocinovic, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%